Analysis of the Sustainability Status of Feed Banks in the 1000 Village Cow Program in Pujut District, Central Lombok: (Dimension of Availability, HR Management, and Production System, Price, Feed Distribution) - Mashur Mashur; Subagio Subagio; Kemas Usman; Hunaepi Hunaepi (IKIP Mataram, 2021)
West Nusa Tenggara Province is one of the centers for beef cattle production in Indonesia, which was set by the Ministry of Agriculture as a pilot program for the 1000 village cattle program in realizing national beef self-sufficiency. The supporting factor for the success of the 1000 village cattle program is the provision of feed throughout the year. The existence of a feed bank is expected to be a solution to overcome the limited supply of feed, especially in the dry season. The Bumbang Wetan Feed Bank in Mertak Village is a feed bank that is expected to supply animal feed needs in five pilot villages of the 1000 village cattle program in Pujut District, Central Lombok Regency. To determine the sustainability status of the feed bank in supporting the 1000 village cattle program, a study was carried out in June-August 2021. The determination of the sustainability status of the feed bank was based on the sensitive attributes of the three dimensions studied, namely: (1) availability of feed ingredients; (2) production, pricing, and distribution systems; (3) HR management. These attributes are arranged referring to the results of primary data collection using a questionnaire. The research method used is descriptive qualitative. Determination of the sustainability status of the feed bank is carried out using the Multi-Dimensional Scaling method with the Rapid Appraisal Beef Cattle Feed Bank Smallholder approach. The results showed that the sustainability value of the three dimensions was 50.59, so it was concluded that the status of the feed bank was in the less sustainable category in supporting the 1000 village cattle program